Design and construction of a data logger based on a speed sensor for DC motor control - Rizki Setiadi; Dony Hidayat Al-Janan; Wirawan Sumbodo; Dimas Eka Firmansyah; Setya Adji Parykesit; Ahmad Azwan; Rian Putra Efendi; Yasir Akmal (JTTM : Jurnal Terapan Teknik Mesin, 2025)
DC motors are actuators that are widely used in many applications, such as robot manipulators, vehicles, and others. DC motor control is generally speed-based. Speed ​​measurement and monitoring in mechanical systems is one of the important aspects. Speed ​​data is not only used to analyze machine performance, but also as a basis for various applications, such as the development of control systems. To improve efficiency, speed measurement for automation technology is very necessary. This study aims to develop a data logger and analyze the response of a DC motor using a speed sensor-based PID control. The method used is experimental. The results of the initial data logger test showed an error rate of 5.63% for wind speed measurements based on speed sensors. The results showed that at a Kp value of 3 approaching stable conditions, it can be used to determine PID control parameters. The error rate of the speed sensor-based data logger with PID control was obtained at 4.67%. PID control is used to control a speed of 200 RPM on a DC motor and the parameters obtained in the PID control system were obtained with a Kp value of 1.8, Ti 1, and Td 0.25